Robotic herding framework design for remote and small-scale pastoral farming - Liu, Jinyu; Chew, Esyin; Sia, Chow Siing; Adli, Hasyiya Karimah; Zhang, Linnan; Gai, Shichen; Yang, Jiaji; Wang, Tao (International Journal of Agricultural and Biological Engineering, 2025)
This study presents a comprehensive framework for designing an intelligent and sustainable robot-assisted herding system, based on a systematic literature review and field investigations conducted in remote pastoral regions operated by small family farms. The study highlights a multi-institutional collaboration between the EUREKA Robotics Centre, Cardiff Metropolitan University, UK; Universiti Malaysia Kelantan; and Shenyang University of Technology, China. The research aims to ensure that advancements in robotic technology are effectively aligned with the practical challenges encountered in livestock herding. The literature review reveals that robotic-assisted herding has evolved from theory to early practical applications through advances in AI, robotics, and agriculture. The study conducted a field survey involving fifty-five farmers, and it revealed low initial awareness from the farmers but high practical acceptance of robotic herding solutions, and challenges in costing and cultural shift. To overcome these challenges, the study applied the integration of object-oriented robotic design with educational initiatives customized to local herding environments. It also coordinated with stakeholders such as farmers, robotic innovators, and local authorities in robotic herding. The proposed framework prioritizes modularity, durability, and adaptability to local context in the robotic design. Future work will focus on iterative development and field trials across China, Malaysia, and the UK. This study is intended to validate and refine the framework. This effort will contribute to global precision livestock farming and the broader transformation toward sustainable agriculture. Key words: smart agriculture; small family farm; herding; animal welfare; interdisciplinary robotics research DOI: 10.25165/j.ijabe.20251806.9826 Citation: Liu J Y, Chew E, Sia C S, Adli H K, Zhang L N, Gai S C, et al. Robotic herding framework design for remote and small-scale pastoral farming. Int J Agric & Biol Eng, 2025; 18(6): 182–190.